Comparison of Two Intraosseous Devices: The NIO Versus the EZ-IO by Novice Users-A Randomized Cross Over Trial. (4th May 2017) - Shina, Avi; Baruch, Erez Nissim; Shlaifer, Amir; Shovali, Ami; Levi, Moran; Yosefy, Or; Segal, David; Bader, Tarif; Shavit, Itai; Yitzhak, Avraham
Abstract: Background : During resuscitation in the field, intraosseous (IO) access may be achieved using a variety of available devices, often attempted by inexperienced users.Aim : We sought to examine the success rate and ease-of-use ratings of an IO device, the NIO® (New Intraosseous Persys Medical, Houston, TX, USA) in comparison to the Arrow® EZ-IO® (Teleflex Medical Research Triangle Park, NC, USA) by novice users.Methods : We performed a randomized crossover trial. The study model was a porcine hind leg which was cut distally in order to expose the marrow. The Study population was composed of pre-graduate medical students without prior experience in IO use, all designated future field physicians. The students underwent instruction and practiced the use of both devices. After practice completion, each student attempted a single IO insertion with both devices sequentially in randomized fashion. Success was defined as a flow of fluid through the bone marrow after a single IO attempt. Investigators which determined the success rate were blinded to the used device.Results : 50 users (33 males, 17 females) participated in the trial, mean age of 21.7 years (±1). NIO users were successful in 92% (46/50) attempts while EZ-IO user success rate was 88% (44/50). NIO success rates were comparable to those of EZ-IO (p = NS). Results were similar when examining only the initial device used. Median score of ease of use was 4 (5 point Likert scale) in both devices (p = NS). 54% (27/50) of the participants preferred using the EZ-IO over the NIO (p = NS).Conclusion : Novice users were equally successful in establishing IO access with the NIO® in comparison to the EZ-IO® in a porcine model.